IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT PJB UBJOM PLTU TENAYAN (STUDI PADA USAHA TENAYAN MANDIRI BUDIDAYA TERNAK LELE, KELURAHAN BENCAH LESUNG KOTA PEKANBARU) - Egi Rugeri; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
PT Pembangkit Jawa Bali CSR Program Operation & Mainstreaming Services Unit of the PLTU Tenayan is a tangible manifestation of the company in carrying out the mandate of the Law and helping to answer community problems in the operational area, especially Bencah Lesung Village, Pekanbaru City. One of the leading CSR programs in the field of empowerment is the Usaha Tenayan Budidaya Ternak Lele. This study aims to determine the stages of implementing the Usaha Tenayan Budidaya Ternak Lele CSR program and to find out the company's motivation for the Usaha Tenayan Mandiri Budidaya Ternak Lele. This study used qualitative research methods. Data collection techniques consist of interviews, observation, and documentation. While the data analysis technique uses descriptive analysis according to Huberman and Miles. For the technique of checking the validity of the data using an extension of participation and triangulation. The results of this study indicate the CSR Team by the Sub Dit & Sekretariat PT PJB UBJOM PLTU Tenayan carried out four stages of implementation in implementing the Usaha Tenayan Mandiri Budidaya Ternak Lele program including: First location selection, which included observation in the target area, collecting social problems, problem planning. Both socialization, which includes the delivery of the results of problem formulation to the target community, counseling about the program to be implemented, and procedures to the community if they want to join the CSR program that will be facilitated by PT PJB UBJOM PLTU Tenayan. Third is community-based development by completing development needs, the development process by clearing land and making ponds and inaugurations attended by relevant stakeholders. Fourth is the independence of society by monitoring CSR programs by companies and increasing income to develop businesses from programs managed by business groups. To see the motivation received by the company by the implementation of theUsaha Tenayan Mandiri Budidaya Ternak Lele program, the company seeks to realize this CSR program to be a piloting project for new groups that will develop the same business, namely in the field of catfish farming in Bencah Lesung. Furthermore, the company will seek the Catfish Livestock CSR program by PT PJB UBJOM PLTU Tenayan as an icon of the Bencah Lesung sub-district so that the people of Pekanbaru city are specifically motivated to develop the business sector in order to improve the economy, by continuing to develop CSR programs through increasing income for community groups managing Usaha Tenayan Mandiri Budidaya Ternak Lele.